Hydrological Simulation and Error Correction in Source Area of Yellow River Based on VIC-BJP Model - ZHU Changchang; HUANG Huaping (Renmin Zhujiang)
The source area of the Yellow River is an important runoff-producing region throughout the Yellow River Basin. Accurate hydrological simulation results of the source area for evaluating regional water resources can provide valuable support to ensure water security and stability in the Yellow River basin. This study employed the VIC model to simulate the daily/monthly runoff process at the Tangnaihai station in the source area of the Yellow River from 2013 to 2022, and based on this, the BJP model was used to correct the errors of the simulation results. Thus, the accuracy of simulation results was improved, and the uncertainty was analyzed quantitatively. Through the comparison between it and the traditional error autoregressive model, some conclusions can be obtained as follows:, (1) The VIC model achieved high accuracy in simulating the flow process of Tangnaihai Station, which suggests that applying this model in the source area is reasonable. (2) Compared with simulation results, the corrected results generated by both the BJP model and the error autoregressive model were improved significantly in accuracy, effectively solving the problem of underestimating the peak water volume in some high flow years. Besides, the accuracy of the BJP model was superior to that of the error autoregressive model. (3) The 90% uncertainty intervals extracted based on the BJP model covered most of the observation points with a narrow bandwidth, and the average bias was less than 0.25. It suggests that the uncertainty analysis results based on the BJP model have a low degree of dispersion, and its corrected results are reasonable and reliable.